ANALYSIS OF THE INFLUENCE OF GOOD CORPORATE GOVERNANCE FOR MANAGEMENTS PROFIT - Arief Kurniawan, 07.05.52.0084; Widati, Listyorini Wahyu (Students Journal of Accounting and Banking, 2012)
This research aims to examine and analyze about the influence of institutional ownership, ownership of the management, the audit committee, the independent Commissioner, and the size of0 the company to profit management. Profit management gives managers the flexibility to protect themselves and the company in anticipation of events that are unexpected for the benefit of the parties involved.The sample in this study is the manufacturing sector companies listed on the Indonesia Stock Exchange during 2008-2010 and obtained as many as 48 companies according to a defined criteria. Sampling techniques using a purposive sampling technique with the company listing criteria during the period of observation, the financial statements are presented in euro, net profit in a row, and have complete data. Engineering analysis used is of multiple regression.The results showed that variable and the audit committee of institutional ownership affect profit management. While the ownership of the management, the independent Commissioner, and company size has no effect on earnings management.Keywords: Institutional Ownership, Ownership Of Manajerial, Committee Audit, Independent Commissary, and Measure Company, Management Profit.